Hubungan Workplace Incivility dengan Karakteristik Demografi: Studi pada Pegawai Polbangtan Manokwari - Khairunisa, Nur Afni; Putri, Anggie Julia; Putri, Fhaujiah Ika Nur Asyah (Jurnal Ilmiah Psikomuda (JIPM) Connectedness, 2024)
Workplace incivility is rudeness experienced by someone at work by their colleagues or superiors. Workplace incivility behavior experienced by employees, either directly or indirectly, will hinder the performance of the employee concerned and the organization's performance in achieving its goals. This research aims to determine the relationship between workplace incivility and demographic characteristics (gender, education level, age and work period) of Polbangtan Manokwari employees. This research used a quantitative approach involving 67 respondents. Data analysis was carried out descriptively, cross tabulation analysis and chi-square test. The research results showed that workplace incivility was not significantly related to the four demographic characteristics studied (P>0.05). This shows that the differences in demographic characteristics of Polbangtan Manokwari employees are not targets for workplace incivility behavior.